Answer:
Please read my updated answer.
I am wasn't sure what you were asking so here and 2 answers.
1st answer ![y=\frac{1}{e}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B1%7D%7Be%7D)
2nd answer ![\frac{dy}{dx}=-\frac{y}{x+7e}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D-%5Cfrac%7By%7D%7Bx%2B7e%7D)
Step-by-step explanation:
![xy+7ey=7](https://tex.z-dn.net/?f=xy%2B7ey%3D7)
![when \\ x=0](https://tex.z-dn.net/?f=when%20%5C%5C%20x%3D0)
Substitute
for
then simplify.
![(0*y)+7ey=7\\ 0+7ey=7\\ 7ey=7](https://tex.z-dn.net/?f=%280%2Ay%29%2B7ey%3D7%5C%5C%200%2B7ey%3D7%5C%5C%207ey%3D7)
Divide each term in
by
and simplify.
![\frac{7ey}{7e}=\frac{7}{7e}](https://tex.z-dn.net/?f=%5Cfrac%7B7ey%7D%7B7e%7D%3D%5Cfrac%7B7%7D%7B7e%7D)
Cancel the common factor of
on the left side.
Rewrite the expression.
![\frac{ey}{e}=\frac{7}{7e}](https://tex.z-dn.net/?f=%5Cfrac%7Bey%7D%7Be%7D%3D%5Cfrac%7B7%7D%7B7e%7D)
Cancel the common factor of
on the left side.
![y=\frac{7}{7e}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B7%7D%7B7e%7D)
Cancel the common factor of 7 on the right side.
Rewrite the expression.
![y=\frac{1}{e}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B1%7D%7Be%7D)
2nd Answer
Step-by-step explanation:
![xy+7ey=7](https://tex.z-dn.net/?f=xy%2B7ey%3D7)
Differentiate both sides of the equation.
![\frac{d}{dx} (xy+7ey)=\frac{d}{dx}(7e)](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%20%28xy%2B7ey%29%3D%5Cfrac%7Bd%7D%7Bdx%7D%287e%29)
Differentiate the left side of the equation.
By the Sum Rule, the derivative of
with respect to x is ![\frac{d}{dx} [xy]+\frac{d}{dx}[7ey]](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%20%5Bxy%5D%2B%5Cfrac%7Bd%7D%7Bdx%7D%5B7ey%5D)
Evaluate ![\frac{d}{dx} [xy]](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%20%5Bxy%5D)
Differentiate using the Product Rule
Rewrite
as
.
![xy'+y+\frac{d}{dx} [7ey]](https://tex.z-dn.net/?f=xy%27%2By%2B%5Cfrac%7Bd%7D%7Bdx%7D%20%5B7ey%5D)
Evaluate ![\frac{d}{dx} [7ey]](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%20%5B7ey%5D)
Since
is constant with respect to
, the derivative of
with respect to
is
.
Reform the equation by setting the left side equal to the right side.
![xy'+7ey'+y=0](https://tex.z-dn.net/?f=xy%27%2B7ey%27%2By%3D0)
Solve for
.
Subtract
from both sides of the equation.
![xy'+7ey'=-y](https://tex.z-dn.net/?f=xy%27%2B7ey%27%3D-y)
Factor
out of
.
![y'x+7ey'=-y](https://tex.z-dn.net/?f=y%27x%2B7ey%27%3D-y)
Factor
out of
.
![y'(x)+y'(7e)=-y](https://tex.z-dn.net/?f=y%27%28x%29%2By%27%287e%29%3D-y)
Factor out
out of ![y'(x)+y'(7e)](https://tex.z-dn.net/?f=y%27%28x%29%2By%27%287e%29)
![y'(x+7e)=-y](https://tex.z-dn.net/?f=y%27%28x%2B7e%29%3D-y)
Divide each term in
by
and simplify.
![\frac{y'(x+7e)}{x+7e} =\frac{-y}{x+7e}](https://tex.z-dn.net/?f=%5Cfrac%7By%27%28x%2B7e%29%7D%7Bx%2B7e%7D%20%3D%5Cfrac%7B-y%7D%7Bx%2B7e%7D)
Cancel the common factor of
.
![y'=-\frac{-y}{x+7e}](https://tex.z-dn.net/?f=y%27%3D-%5Cfrac%7B-y%7D%7Bx%2B7e%7D)
Replace
with ![\frac{dy}{dx}=-\frac{y}{x+7e}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D-%5Cfrac%7By%7D%7Bx%2B7e%7D)
![\frac{dy}{dx}=-\frac{y}{x+7e}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D-%5Cfrac%7By%7D%7Bx%2B7e%7D)